1983
DOI: 10.1056/nejm198309293091302
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New Bipyridine Inotropic Agent — Milrinone — in Patients with Severe Congestive Heart Failure

Abstract: Milrinone, a derivative of amrinone, has nearly 20 times the inotropic potency of the parent compound and does not cause fever or thrombocytopenia in normal volunteers or in animals sensitive to amrinone. In 20 patients with severe congestive heart failure, intravenous milrinone resulted in significant decreases in left ventricular end-diastolic pressure (from 27 +/- 2 to 18 +/- 2 mm Hg), pulmonary wedge pressure, right atrial pressure, and systemic vascular resistance, as well as a slight reduction in mean ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(75 citation statements)
references
References 30 publications
3
72
0
Order By: Relevance
“…We have observed that an excessive reduction in left heart filling pressure with intravenous administration of milrinone can result in a marked attenuation of the drug's apparent positive inotropic effect as reflected by peak positive dP/dt.25 Thus an excessive reduction in preload caused by the intravenous administration of a cardiac bipyridine, particularly in a patient whose initial filling pressures are not elevated, could obscure the drug's positive inotropic action. With regard to the few patients who did demonstrate an apparent positive inotropic response in the study of Wilmshurst et al, 3 it was postulated that increased contractility was the result of an indirect effect of the drug to increase sympathetic tone. '6 This mechanism cannot explain the positive inotropic effects of intracoronary infusion of milrinone in the present study because there were significant decreases in both heart rate and norepinephrine levels, suggesting that sympathetic tone was actually reduced, most likely due to reflex withdrawal.…”
Section: Methodsmentioning
confidence: 99%
“…We have observed that an excessive reduction in left heart filling pressure with intravenous administration of milrinone can result in a marked attenuation of the drug's apparent positive inotropic effect as reflected by peak positive dP/dt.25 Thus an excessive reduction in preload caused by the intravenous administration of a cardiac bipyridine, particularly in a patient whose initial filling pressures are not elevated, could obscure the drug's positive inotropic action. With regard to the few patients who did demonstrate an apparent positive inotropic response in the study of Wilmshurst et al, 3 it was postulated that increased contractility was the result of an indirect effect of the drug to increase sympathetic tone. '6 This mechanism cannot explain the positive inotropic effects of intracoronary infusion of milrinone in the present study because there were significant decreases in both heart rate and norepinephrine levels, suggesting that sympathetic tone was actually reduced, most likely due to reflex withdrawal.…”
Section: Methodsmentioning
confidence: 99%
“…Recently their clinical efficacy has been challenged (Editorial, 1978;Editorial, 1979;Petch, 1979) and at the same time vasodilators (Franciosa, 1982;Packer & Le Jemtel, 1982;Packer, 1983) and positive inotropic drugs have become available as alternative treatments (Baim et al, 1983;Dawson et al, 1983). In addition the understanding of the pathophysiology of heart failure has advanced (Harris, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…2 The clinical response of patients with congestive heart failure who are treated with this agent has been ascribed to readily demonstrable improvements in indexes of left ventric-ular systolic function (including increases in peak positive dP/dt and in left ventricular ejection fraction) and concurrent arteriolar vasodilation. 3 However, possible effects of milrinone on ventricular diastolic function, which might also contribute to the hemodynamic response to this agent, have not been evaluated. In particular, improved diastolic relaxation and distensibility might lead to more effective sarcomere stretch within the ventricular myocardium and to better systolic performance.6 7 Thus it is possible that improved systolic pump function in patients with heart failure treated with milrinone might reflect a complex interaction of effects of the drug on systolic and diastolic properties of the ventricular myocardium as well as changes in the peripheral vasculature.…”
mentioning
confidence: 99%